Starting at home : caring and social policy - Noddings, Nel (University of California Press, 2002)
Nel Noddings, one of the central figures in the contemporary discussion of ethics and moral education, argues that caring--a way of life learned at home--can be extended into a theory that guides social policy. Tackling issues such as capital punishment, drug treatment, homelessness, mental illness, and abortion, Noddings inverts traditional philosophical priorities to show how an ethic of care can have profound and compelling implications for social and political thought.